Exam Warriors - Narendra Modi (Penguin, 2018)
India is the world's most youthful nation, with two-thirds of our population under the age of thirty-ﬁve. Young Indians have distinguished themselves in a wide range of ﬁelds not only in India but also overseas. It is the strength and skills of these youngsters that will usher in a New India. Interacting with the youth is something I have always enjoyed. That is why, in February 2015, I decided to devote that month's 'Mann Ki Baat' programme to students appearing for their board examinations. In India, these exams are typically held around late February and early March. 'Mann Ki Baat', I thought, could be a wonderful medium to talk directly to students who were appearing for the exams and support them during this crucial phase of their lives. It was an experiment of sorts and the end result was very encouraging. The response to that particular 'Mann Ki Baat' was overwhelming. Before the programme, several students from all over India shared their thoughts through letters, emails and MyGov. Parents and teachers wrote congratulatory messages to me for taking up an issue that deserved attention.